Do Islamic Banks Outperform Commercial Banks? Longitudinal Managerial and Profitability Efficiencies and Risk Management - Qian, Long Kweh; Wen-Min, Lu; Mohd Hisyam, Ghazali @ Mohd Zain; Noor Azlinna, Azizan (2014)
This study assess the managerial efficiency and profitability efficiency of 14 commercial banks and 9 Islamic banks in Malaysia using a dynamic DEA model with network structure within the slacks-based measure (the DNSBM model). In estimating the efficiencies, we also take into consideration two risk factors: asset risk and liability risk. Moreover, t his study examines the impact of risk management on operating performance using truncated regression with a bootstrapping procedure for the period 2008-2012. The efficiency scores show that our sampled banks should first focus on improving their managerial efficiency, and then their profitability efficiency to enhance their overall operating performance. The results also show that the risk measures have significant impacts on bank efficiency. Islamic banks have better managerial efficiency but lower profitability efficiency. We also include frontier projections of banks that highlight areas of focus. Our regression analysis reveals that the size and independence of risk management committee are significantly positively associated with operating performance. However, the number of meeting conducted by risk management committee has a si gnificantly inverse relationship with operating performance. Overall, bank managers should manage well risks to gain a competitive advantage and ultimately to achieve better operating performance.